Production planning improvement in a t-shirt printing company using Material Requirement Planning (MRP) approach: a case study - Sulau Padan, Cassandra; Su’ai @ Suani, Nur Ratna; Ruselan, Mohammad Fahmi; Nordin, Muhammad Daud; Raja Mamat, Tengku Nur Azila; Mahmood, Salwa; Mat Hassan, Nik Normunira (Penerbit UTHM, 2022)
Material requirement planning (MRP) is one of production planning and control (PPC) concept used for short-term scheduling. Sibawaih Ventures faced problem in handling customer order when their business receive more order than usual. A case study is conducted to T-shirt A production to assist Sibawaih Ventures in planning their production. By studying product structure of T-shirt A and dependency of each part, as well as lead time required to complete T-shirt A, MRP schedule is generated. MRP schedule shows that, Sibawaih Ventures can produce 800 tshirts in 7 days time, thus, customer orders can be met in a timely manner. MRP schedule provides all information provided by production people to run production, while management can use MRP schedule to control and monitor production accordingly.